Stadium Violence in Football Leagues in the Kurdistan Region – Iraq from the Perspective of Stakeholders (Causes – Solutions) - Kemal, Asst.Prof.Dr. Diyar Kemal Asaad (Sulaimani Journal for Humanities, 2025)
Hooliganism in stadiums is the most common phenomenon at present. It is a social, psychological, and possibly political phenomenon in Iraq in general, and in Iraq in particular, specifically in the provinces of the Kurdistan Region of Iraq. It has started to emerge in many matches of the Kurdistan Region League, posing a danger to the lives of spectators, referees, players, and everyone involved in football activities. This may be attributed to the behavior of players and administrators, the incompetence of referees, the lack of sports culture among fans, and the failure of media professionals to perform their role properly. The researcher used the descriptive method with a survey approach (case study) due to its suitability for the nature of the problem. The researcher deliberately chose the research community from (administrators – coaches – players – referees – media professionals – spectators) in the provinces of the Kurdistan Region of Iraq, totaling (408) individuals representing all the provinces. The researcher selected (360) of them as the research sample after excluding those who participated in the exploratory experiment, numbering (48). To collect data, the researcher used scales related to measuring stadium hooliganism, and to process the data, a statistical package was used. In light of the results, he reached a number of conclusions and recommendations.